Новий підхід в оцінці обсягів руху в Україні - Ройко, Юрій; Давосир, Владислав; Євчук, Юрій (Посвіт, 2019)
Topical question is staying the determination of existing and forecasting traffic volumes which is one of the main criteria of planning the development of city road networks and out-of-town roads. This traffic volume can be expressed through the motorization level and also the amount of fuel realization. Also the important task is establishment of mutual connection between traffic volumes and the level of traffic safety on transport networks.
A new appoach in evaluation the traffic volume in Ukraine
Keywords: 656.13